The Effect of Sonication on Acoustic Properties of Biogenic Ferroparticle Suspension - JÓZEFCZAK, Arkadiusz; HORNOWSKI, Tomasz; KRÓL, Anita; MOLČAN, Matúš; LESZCZYŃSKI, Błażej; TIMKO, Milan (Archives of Acoustics, 2016)
Superparamagnetic iron oxide nanoparticles (SPION) synthesised chemically usually need the modification of the particle surface. Other natural sources of magnetic particles are various magnetotactic bacteria. Magnetosomes isolated from magnetotactic bacteria are organelles consisting of magnetite (Fe_3O_4) or greigite (Fe_3S_4) crystals enclosed by a biological membrane. Magnetotactic bacteria produce their magnetic particles in chains. The process of isolation of magnetosome chains from the body of bacteria consists of a series of cycles of centrifugation and magnetic decantation. Using a high-energy ultrasound it is possible to break the magnetosome chains into individual nanoparticles – magnetosomes. This study presents the effect of sonication of magnetosome suspension on their acoustic properties, that is speed and attenuation of the sound. Acoustic propagation parameters are measured using ultrasonic spectroscopy based on FFT spectral analysis of the received pulses. The speed and attenuation of ultrasonic waves in magnetosome suspensions are analysed as a function of frequency, temperature, magnetic field intensity, and the angle between the direction of the wave and the direction of the field.